Effects of tandem walk and cognitive and motor dual- tasks on gait speed in individuals with chronic idiopathic neck pain: a preliminary study - Munlika Sremakaew (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. Introduction: Gait impairment has been associated with neck pain. It is relevant to understand the possible influence of narrow-based walk and an attention-demanding secondary task on gait performance in neck pain. Purpose: To investigate the effects of tandem walk and cognitive and motor dual-tasks on gait speed in persons with chronic idiopathic neck pain (CINP) compared with controls. Methods: A cross-sectional study. Thirty participants with CINP and 30 asymptomatic controls participated in the study. Gait speed was assessed using a timed 10-m walk test at a comfortable pace under four conditions: (1) comfortable walk (as reference); (2) tandem walk (single task); (3) cognitive dual-task walking; and (4) motor dual-task walking. Dual-task interference was calculated. Results: There was no difference in comfortable gait speed between groups (p= 0.40). The CINP group had slower gait speed during the tandem walk than controls (p= 0.02). The dual-task interference on gait speed was not different between groups (p = 0.67 for cognitive, p = 0.93 for motor). Conclusion: Participants with CINP had impaired gait stability during tandem walk. An attention-demanding secondary task did not influence gait speed in individuals with CINP compared to controls. The study suggests that tandem walk could be considered as an assessment tool and part of rehabilitation for neck pain.